2017
DOI: 10.1097/iae.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphopsia and Tangential Retinal Displacement After Epiretinal Membrane Surgery

Abstract: The degree of metamorphopsia significantly correlated with the tangential retinal displacement. Dislocated Müller cells may stimulate the photoreceptors located away from original positions, which consequently results in the sensation of metamorphopsia in patients with an epiretinal membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 22 publications
1
47
0
3
Order By: Relevance
“…At the same time, a statistically significant increase of the thickness of the retina in the fovea щину сітчастої оболонки та порушення структури окремих її шарів [11][12][13][14][15] Водночас, виявлено статистично достовірне збільшення товщини сітчастої оболонки у фове was detected in comparison with non irradiated control ( Table 1). Fig.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…At the same time, a statistically significant increase of the thickness of the retina in the fovea щину сітчастої оболонки та порушення структури окремих її шарів [11][12][13][14][15] Водночас, виявлено статистично достовірне збільшення товщини сітчастої оболонки у фове was detected in comparison with non irradiated control ( Table 1). Fig.…”
Section: Resultsunclassified
“…Such an increase can significantly affect the functional status of the retina, since the parameters of struc tures closely related to photoreceptors change. In addition, the optical function of the retina's struc tures is important, suggesting that change in the thickness of the retina in the macular zone may be the cause of the appearance of metamorphopsy (distortion of the shape and size of objects) [13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In the present study, the ONL-B is more evident in ERM patients, the average axis was 2 degrees from the horizontal line, and 90% of ERM patients showed an axis within ± 45 degrees, which may be due to the ERM contraction direction. Our colleague recently reported that the vertical retinal displacement was greater than the horizontal retinal displacement, as assessed by measuring the position of the retinal vessels in ERM patients 17 , which indicates that retinal morphology is likely to deform to be horizontally long with ERM vertical contraction. The results of the present study are consistent with this observation.…”
Section: Discussionmentioning
confidence: 96%